(untitled) (Research, Society and Development, 2022)
Increased prevalence of diabetes mellitus mortality in developing countries has been observed in recent decades. This is largely due to the accelerated demographic and epidemiological transition process underway linked to other diseases aggravated by diabetes. The present work is a ecological study that had as its main objective to analyze the mortality by Diabetes Mellitus in the State of Piauí in the period from 2009 to 2019, describing the sex, age group, year and place of death and variations of the type of Diabetes according to the International Statistical Classification of Diseases and Health-Related Problems, Tenth Revision (ICD-10) codes E10 to E14 and indicators as secondary objectives. In a quantitative approach to obtain data on mortality, information was used from deaths reported to the Mortality Information System (SIM) and the Brazilian Institute of Geography and Statistics (IBGE) as a source of data for population estimates and territorial density, as well as the DATASUS/TABNET platform of the Brazilian Ministry of Health. According to the data obtained, it was found that the state of Piauí reached 13,131 deaths from Diabetes mellitus during the period studied, being verified the predominance of women 56%, compared to men who represent 44%, the highest prevalence occurred in the mid-north region. In addition, there was an increase in the mortality rate in the period studied, observing a slight decrease in 2018, confirming a public health problem in the State of Piauí.